Global Research Trend in Sustainable Tourism Marketing: A Bibliometric Approach - Tazkiyah Rizqi Alawi; Lissa Rosdiana Noer (Journal Research of Social Science, Economics, and Management, 2025)
The growing importance of sustainability in the global tourism industry has led to a surge of research exploring how marketing contributes to sustainable destination development. This study aims to analyze the evolution, trends, and emerging themes in sustainable tourism marketing from 2015 to 2025. Using data retrieved from 305 Scopus database, a bibliometric analysis was conducted through performance analysis and science mapping (keyword co-occurrence and bibliographic coupling) using VOSviewer software. The findings reveal a steady growth of publications over the last decade, with major contributions originating from the United Kingdom, Poland, China, and Spain. The most influential journals include Sustainability (Switzerland), Journal of Sustainable Tourism, and Tourism Management Perspectives. Four dominant thematic clusters were identified: environmental and cultural sustainability, marketing and communication strategies, community-based governance, and post-pandemic behavioral adaptation. These findings indicate that sustainable tourism marketing has evolved into an interdisciplinary research domain bridging sustainability, consumer behavior, and destination branding. This study provides an integrated overview of the intellectual structure of sustainable tourism marketing, serving as a reference for academics, policymakers, and practitioners in designing evidence-based and competitive sustainability strategies.